Examining the decay in serum ferritin following intravenous iron infusion: a retrospective cohort analysis of Olympic sport female athletes - McKay, A. K. A.; Goods, P. S. R.; Binnie, M. J.; Goodman, C.; Peeling, P. (Applied Physiology, Nutrition, and Metabolism, 2020)
The long-term decay rate of serum ferritin post-iron infusion in athletic populations is currently unknown. Here, we modelled the decay rate of serum ferritin in female athletes after an intravenous iron infusion (n = 22). The post-infusion serum ferritin response and the rate of decay was highly variable between athletes; however, we demonstrate that follow-up blood testing at 1 (154 µg/L; 77-300 µg/L) and 6 months (107 µg/L; 54-208 µg/L) post-infusion is appropriate to observe treatment efficacy and effectiveness. Novelty: Female athletes should have serum ferritin assessed at 1 and 6 months following an intravenous iron infusion to determine efficacy and effectiveness